Penerapan Metode Khotbah Alkitabiah Untuk Meningkatkan Partisipasi Â Jemaat - Kristin, Violentina; Andi Yusuf, Etni Grace (Sekolah Tinggi Teologi Berita Hidup, 2023)
The purpose of this study is to determine how the application of biblical preaching methods to increase congregational participation. Methods can help a preacher in conveying God's intentions, goals and messages to the congregation so that the congregation can receive and understand what is conveyed from the sermon. Preaching is a communication process that has a divine dimension. In this case, God, as Creator and Redeemer, continuously communicates through His word to mankind, through a preacher. Thus, preaching can be viewed as a communication process consisting of the text of the Bible (God's Word) as a source of news, messages, and recipients of messages. More often than not, preaching is understood as humans talking about God, but in fact preaching is about God speaking to humans through a preacher. This study uses qualitative methods to reveal data. The results of this study indicate that the application of methods in preaching to increase congregational participation in responding to sermons.